Impact of infiltration parameters and Manning roughness on the advance trajectory and irrigation performance for closed-end furrows - Nie, Weibo; Fei, Liangjun; Ma, Xiaoyi (Spanish journal of agricultural research : SJAR, 2014)
Evaluation of furrow irrigation systems requires accurate estimation of soil infiltration parameters and Manning roughness, and the impact of variations of those parameters should be considered. The objectives of this paper were to verify the reliability of the infiltration parameters and Manning roughness estimated with SIPAR_ID software, and to analyze the impacts of different combinations between soil infiltration parameters and Manning roughness on the water trajectory and irrigation performance for closed-end furrows. The study consisted of field experiments and numerical simulation. Field experiments using Fuji apple trees were conducted in three villages of the Yangling district in October 2007. Infiltration parameters and Manning roughness were estimated with SIPAR_ID software. The estimated values were input into the WinSRFR software, and the advance trajectory and flow depths in the upstream were simulated on each furrow. The results show that the simulated values with WinSRFR software were in good agreement with measured data. Thus, the infiltration parameters and Manning roughness estimated with SIPAR_ID software were reliable. It was found that the water advance trajectory and the irrigation performance were not sensitive to variations of Manning roughness, but they were very sensitive to the variation of soil infiltration parameters laterally across the field between the furrows. Therefore, the average of Manning roughness on the whole field can be used as a representative value to simulate the advance trajectory and irrigation performance for every furrow. However, during the simulations, the variations of the soil infiltration parameters for different furrows across the field must be taken into account. Otherwise, significant errors can be produced in the simulated water advance trajectory and irrigation performance.